2018
DOI: 10.1080/20002297.2018.1502027
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo anti-inflammatory effects of probiotics for periodontal health

Abstract: Background: Probiotic bacteria with anti-inflammatory properties have the potential to be of therapeutic benefit in gingivitis.Objective: To evaluate the effects of potential probiotic strains on inflammatory mediators involved in early gingivitis using an ex vivo inflammation model.Methods: Strains were screened in viable and attenuated forms for effects on bacterial lipopolysaccharide (LPS)-stimulated release of interleukins (IL)-1β, -6 and -8, tumor necrosis factor-α, prostaglandin E2 and 8-isoprostane from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 25 publications
2
20
0
2
Order By: Relevance
“…The model used is well established for testing anti‐inflammatory effects of compounds as it examines various inflammatory mediators. 58 , 59 Parameters such as PGE2 and IL‐1 are known to play a crucial role in gingivitis. The in vitro results showed that the tested extracts potently prevented both PGE2 and IL‐1 release.…”
Section: Discussionmentioning
confidence: 99%
“…The model used is well established for testing anti‐inflammatory effects of compounds as it examines various inflammatory mediators. 58 , 59 Parameters such as PGE2 and IL‐1 are known to play a crucial role in gingivitis. The in vitro results showed that the tested extracts potently prevented both PGE2 and IL‐1 release.…”
Section: Discussionmentioning
confidence: 99%
“…The probiotics have been shown to possess anti-inflammatory and immune-modulatory properties (Akour, 2020;Khaneghah et al, 2020). Mounting shreds of evidence from several in vitro studies suggest that the active anti-inflammatory role of probiotics by suppression of pro-inflammatory cytokine expression and reduction in the release of inflammatory mediators (Schmitter et al, 2018;Yu et al, 2019).…”
Section: Nutraceutical Approaches For Attenuation Of Inflammatory Responses Probioticsmentioning
confidence: 99%
“…development of gingivitis and stimulates an inflammatory response in host cells. 37 The mechanism by which these strains can inhibit the LPS-stimulated release of inflammatory mediators from host cells has not been revealed and warrants investigation in future studies. However, previous research showed that probiotic strains used in the gut can interact with toll-like receptors on host cells to downregulate the expression of nuclear factor-kappa-B and proinflammatory cytokines.…”
Section: Synbiotic and Periodontal Indicesmentioning
confidence: 99%